Physical Degradation of Toli Shad Gillnet: Breaking Strength, Elongation, and Fisheries Implications - Mardiah, Ratu Sari; Park , Subong; Yurizal , Yurizal; Nugraha , Erick; Rasdam , Rasdam; Prasetyo, Ganang Dwi; Khikmawati, Liya Tri; Febriyanto , Fredi; Purwanto , Yuli; Isman, Khairudin (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Synthetic nets, widely used in aquaculture and marine fishing, experience reduced performance over time due to environmental exposure. The study analyzes the effectiveness of Toli shad gillnets based on their technical age using statistical and experimental methods. A strong negative correlation exists between technical age and both breaking strength (r = -0.972) and elongation (r = -0.92). Toli shad gillnets perform optimally within 2 to 3 years of use, with effectiveness declining by the fourth year as indicated by scores of 40–59, suggesting adequate performance but the need for targeted improvements. Medium-term maintenance should be performed annually throughout the net’s service life, up to a maximum of 7 years, while replacement is recommended starting in the 4 year to mitigate performance degradation. Abstract Synthetic nets have high elasticity and are widely used for both aquaculture and marine fishing. However, as their technical age increases, their performance declines due to wear, reduced breaking strength, and decreased elongation caused by continuous exposure to the marine environment. Monitoring the technical age of nets is crucial to maintaining the effectiveness of Toli shad gillnets, minimizing losses, and ensuring optimal catch yields. This study aims to examine the physical degradation of synthetic gillnets used in Toli shad (Tenualosa macrura) fisheries based on their technical age. This study utilized gillnets targeting toli shad (Tenualosa macrura), with varying technical ages (control net, 1-year, 2-year, and 3-year nets), all made from polyamide (PA) monofilament. The differences in net dimensions were attributed to variations in their service life. The method used is purposive sampling, analyzed using descriptive statistics, correlation analysis, a Completely Randomized Design (CRD), and effectiveness evaluation. The results show that the structure of Toli shad gillnets consists of mesh sizes of 77.82–99.60 mm, thread diameters of 0.34–0.53 mm, and knot heights of 1.52–2.28 mm. The relationship between technical age and breaking strength has a correlation coefficient (r) of -0.972, an R² of 0.94, and a regression equation of y = 9.85 - 1.31x. The LSD test indicates a significant difference in breaking strength across treatments. The correlation between technical age and elongation has an r-value of -0.92, an R² of 0.86, with the equation y = 20.11 - 0.34x. The LSD test shows that the control net has significantly different elongation compared to others, but nets aged 1, 2, and 3 years show no significant differences. The study concludes that Toli shad gillnets remain effective for up to 3–4 years, with an effectiveness value of ≥50%. The implications of this study contribute to the efficient management of fishing nets by informing maintenance and replacement strategies based on the technical age and mechanical degradation of the gear. These findings suggest the importance of integrating net lifespan into gear management to enhance catch performance and sustainability in small-scale fisheries.